Efficient modulation of the magnetocaloric refrigerator capacity. (January 2023) - Masche, M.; Liang, J.; Engelbrecht, K.; Bahl, C.R.H.
Highlights: New insights into the part-load operation of a magnetocaloric cooling device. Experimental capacity modulation by tuning the fluid flow rate and cycle frequency. Reducing the capacity to 54 % of the maximum load nearly doubles the efficiency. A maximum second-law efficiency of 29.7 % was achieved at a 14 K temperature span. Part-load operation with large energy-saving potential. Abstract: Magnetocaloric energy conversion devices (e.g., room air conditioners and household refrigerators) have the potential to significantly reduce the emissions associated with refrigerant leakage into the atmosphere but still have lower efficiencies compared to mature vapor compression systems. The efficiency of a magnetocaloric cooling device derives not only from its design characteristics (e.g., solid refrigerant, hydraulic system, and magnet system) and its operating temperature span but also from its modulating capability. Owing to the lack of experimental data regarding this topic, the advantage of modulating the cooling capacity (i.e., the part-load performance) of an active magnetic regenerator prototype is demonstrated experimentally for the first time. The capacity modulation is carried out by means of regulating both the cycle frequency of the device and the volumetric flow rate of the heat transfer fluid. At a 14 K temperature span and a 1.4 Hz frequency, the magnetocaloric refrigerator prototype using 3.8 kg of gadolinium provided a maximum cooling capacity of 452 W with an appreciable coefficient of performance of 3.2, which corresponds to a second-law efficiency of 15.5 %. At part-load operating conditions, the device can produce a cooling capacity of 245 W with an increased second-law efficiency of 29.7 %, or a coefficient of performance of 6.2, making it more competitive with traditional vapor compression systems. In future studies, the experimental data obtained may be implemented in a dynamic building energy model to quantify the energy-saving benefits of part-load operation by estimating the overall system efficiency during a typical cooling season.